Study on Anti-inflammatory and Anti-oxidative Stress Mechanism of Sitagliptin: a Dipeptidyl Peptidase-4 Inhibitor - ZHU Jing, XIE Ji, HU Xiaoxia (Zhongguo quanke yixue)
The prevalence rate of type 2 diabetes is increasing year by year. It is known that oxidative stress and inflammation can participate in the occurrence and development of diabetes. Dipeptidyl peptidase-4 (DPP-4) inhibitors can enhance the incretin effect by inhibiting DPP-4, thus playing a hypoglycemic role, and have been widely used in the treatment of diabetes patients. Currently, studies have shown that DPP-4 expression is up-regulated in a variety of inflammatory diseases, suggesting that it may be involved in the occurrence of inflammation. However, there are few relevant reports on the mechanism of action of DPP-4 inhibitor in inflammation and oxidative stress. Therefore, this paper reviews the anti-inflammatory and antioxidant stress mechanism of sitagliptin, a DPP-4 inhibitor, and proposes that sitagliptin has certain application prospects in the treatment of other diseases, providing references for subsequent relevant studies.